Emission of trace gases and aerosols from biomass burning – an updated assessment - Andreae, Meinrat O. (Atmospheric chemistry and physics, 2019)
Since the publication of the compilation of biomass burning emission factors by Andreae and Merlet (2001), a large number of studies have greatly expanded the amount of available data on emissions from various types of biomass burning. Using essentially the same methodology as Andreae and Merlet (2001), this paper presents an updated compilation of emission factors. The data from over 370 published studies were critically evaluated and integrated into a consistent format. Several new categories of biomass burning were added, and the number of species for which emission data are presented was increased from 93 to 121. Where field data are still insufficient, estimates based on appropriate extrapolation techniques are proposed. For key species, the updated emission factors are compared with previously published values. Based on these emission factors and published global activity estimates, I have derived estimates of pyrogenic emissions for important species released by the various types of biomass burning.